A Jewish Religious Perspective on Cellular Agriculture - Kenigsberg, Joel A.; Zivotofsky, Ari Z. (Frontiers in Sustainable Food Systems, 2020)
Clean Meat is an emerging technology which promises to revolutionize the global food market. Alongside technological developments, the social impact of this innovation is being explored. Consumer acceptance will depend on multiple factors. For Orthodox Jews, the critical question will be whether the new food can be defined as kosher. In the absence of an exact precedent in Talmudic case law, scholars have begun to examine which set of principles would govern the status of the new meat product. Traditionally, meat is permitted for kosher consumption only when it derives from a kosher species which has been kosher slaughtered in accordance with strict regulations. There is room to suggest that this same set of rules would determine the status of any product derived through cellular agriculture, and thus the source cells would have to be extracted from a kosher species and only after kosher slaughter. Another approach would be to view the process as so different from the traditional growth of meat that it may be defined as kosher, even where traditional meat would not. Three determining factors will be: (1) the source of the original cells from which clean meat will be produced (animal species and cell type), (2) the nature of the growth medium, and (3) the exact nature of the process involved, which will determine whether the final product is considered a “new entity” or merely an “inheritance” of the starter cells. An authoritative ruling must be based on an in-depth appreciation of the scientific methods involved.